Life during wartime: Emotions and the development of act up - Gould, Deborah (Mobilization: An International Journal, 2002)
Focusing on the street AIDS activist movement ACT UP, this article explores the question of social movement sustainability. Emotions figure centrally in two ways. First, I argue that the emotion work of movements, largely ignored by scholars, is vital to their ability to develop and thrive over time. I investigate the ways AIDS activists nourished and extended an “emotional common sense” that was amenable to their brand of street activism, exploring, for example, the ways in which ACT UP marshaled grief and tethered it to anger; reoriented the object of gay pride away from community stoicism and toward gay sexual difference and militant activism; transformed the subject and object of shame from gay shame about homosexuality to government shame about its negligent response to AIDS; and gave birth to a new “queer” identity that joined the new emotional common sense, militant politics, and sexradicalism into a compelling package that helped to sustain the movement. Second, I investigate the emotions generated in the heat of the action that also helped the street AIDS activist movement flourish into the early 1990s.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; VIH; amériques; approches et analyses; identités LGBTQIA2+; militance; mouvements sociaux; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; émotions; états-unis

La "conscientisation" dans le militantisme des années 1970 - Mathieu, Lilian (Discours savants, discours militants: mélange des genres, 2002)
"OGM, nucléaire, principe de précaution, comité de sages, experts… autant de figures ou de domaines pour lesquels science et politique sont étroitement imbriquées. Le recours dans le débat public à la science et à l'expertise semble constituer une ressource politique susceptible de convaincre efficacement. Les auteurs montrent la diversité des usages militants des discours savants et saisissent les conditions de " passage " des discours d'un univers à l'autre."-- Site de l'éditeur.
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; justice sociale; militance; pédagogie; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Loving internationalism: The emotion culture of transnational women's organizations, 1888-1945 - Taylor, Verta; Rupp, Leila (Mobilization: An International Quarterly, 2002)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; allemagne; amériques; angleterre; discipline; droits des femmes*; europe; femmes* trans; france; militance; pays-bas; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; états-unis